Endometrial stem/progenitor cells in menstrual blood and peritoneal fluid of women with and without endometriosis. Issue 1 (July 2021) - Masuda, Hirotaka; Schwab, Kjiana E.; Filby, C.E.; Tan, Charmaine S.C.; Tsaltas, Jim; Weston, Gareth C.; Gargett, Caroline E.
Highlights: Evidence of retrograde menstruation of endometrial stem/progenitor cells SUSD2 + and N-cadherin + cells in menstrual blood and peritoneal fluid during menses Endometrial CFU are present in menstrual blood and peritoneal fluid during menses Endometrial CFU persisted in peritoneal fluid after menses in endometriosis women Clonogenic endometrial cells were not detected in peripheral blood Abstract: Research question: Are endometrial stem/progenitor cells shed into uterine menstrual blood (UMB) and the peritoneal cavity in women with and without endometriosis during menstruation? Design: Women with ( n = 32) and without endometriosis ( n = 29) at laparoscopy (total 61), carried out during the menstrual ( n = 41) and non-menstrual phase ( n = 20) were recruited. The UMB, peritoneal fluid and peripheral blood were analysed by clonogenicity assay and flow cytometry to quantify the concentrations of endometrial clonogenic cells, SUSD2 + mesenchymal stem cells (eMSC) and N-cadherin + epithelial progenitor cells (eEPC). Results: Clonogenic endometrial cells, eMSC and eEPC were found in most UMB samples at similar concentrations in women with and without endometriosis. In contrast, 62.5% of women with endometriosis and 75.0% without (controls) had clonogenic cells in peritoneal fluid samples during menses. The eMSC were present in the peritoneal fluid of 76.9% of women with endometriosis and 44.4% without, and eEPC were found in the peritoneal fluid of 60.0% of women with and 25.0% without endometriosis during menses. Median clonogenic, eMSC and eEPC concentrations in peritoneal fluid were not significantly different between groups. More clonogenic cells persisted beyond the menstrual phase in the peritoneal fluid of women with endometriosis (menstrual 119/ml [0–1360/ml] versus non-menstrual 8.5/ml [0–387/ml]; P = 0.277) compared with controls (menstrual 76.5/ml [1–1378/ml] versus non-menstrual 0/ml [0–14/ml]; P = 0.0362). No clonogenic endometrial cells were found in peripheral blood. Conclusions: Clonogenic endometrial cells, SUSD2 + eMSC and N-cadherin + eEPC are present in UMB and the peritoneal fluid of women with and without endometriosis. Further study of the function of these cells may shed light on the cellular origins of endometriosis.